2006
DOI: 10.1111/j.1460-9568.2006.05043.x
|View full text |Cite
|
Sign up to set email alerts
|

PIP3EA and PD‐168077, two selective dopamine D4 receptor agonists, induce penile erection in male rats: site and mechanism of action in the brain

Abstract: PIP3EA (2-[4-(2-methoxyphenyl)piperazin-1-yl-methyl]imidazo[1,2-a]pyridine) and PD-168077 (N-[4-2-cyanophenylpiperazin-1-ylmethyl]-3-methylbenzamide maleate), two selective dopamine D4 agonists, administered systemically, intracerebroventricularly or into the paraventricular nucleus of the hypothalamus induce penile erection in male Sprague-Dawley rats. A U-inverted dose-response curve was found with either compound when given subcutaneously (1-100 microg/kg) or intracerebroventricularly (0.1-20 microg/rat), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 49 publications
4
53
1
Order By: Relevance
“…In agreement with this notion but contrary to previous findings Melis et al, 2005;EnguehardGueiffier et al, 2006), all of the highly selective D 4 agonists failed to induce PE. It should be noted, however, that the maximal PE responses for apomorphine, quinpirole, and pramipexole were lower than some previous reports (e.g., Melis et al, 2006), suggesting procedural differences may have affected the PE response. Nevertheless, the percentage incidences of PE for apomorphine and the D 3 -preferring agonists were similar to previous reports (e.g., Hsieh et al, 2004), suggesting that any procedural differences only affected the maximal number of PEs observed, not the absolute capacity of the agonists to induce PE.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…In agreement with this notion but contrary to previous findings Melis et al, 2005;EnguehardGueiffier et al, 2006), all of the highly selective D 4 agonists failed to induce PE. It should be noted, however, that the maximal PE responses for apomorphine, quinpirole, and pramipexole were lower than some previous reports (e.g., Melis et al, 2006), suggesting procedural differences may have affected the PE response. Nevertheless, the percentage incidences of PE for apomorphine and the D 3 -preferring agonists were similar to previous reports (e.g., Hsieh et al, 2004), suggesting that any procedural differences only affected the maximal number of PEs observed, not the absolute capacity of the agonists to induce PE.…”
Section: Discussioncontrasting
confidence: 47%
“…Although Ro 61-6270 has not been characterized extensively (Clifford and Waddington, 2000), L-745,870 has been shown to possess favorable pharmacokinetics (0.3 mg/kg p.o. is thought to be sufficient to occupy ϳ90% of D 4 receptors; Patel et al, 1997) and has been shown to inhibit PD-168,077-and PIP3EA-induced PE at a dose of 1.0 mg/kg Melis et al, 2006), suggesting that the doses used in the current studies were sufficient to block D 4 receptors. Together with previous reports that L-745,870 was unable to alter apomorphine-induced PE , the current studies suggest that the proerectile effects of D 2 -like agonists (e.g., apomorphine and pramipexole) are mediated by activation of the D 3 , but not the D 4 , receptor.…”
Section: Discussionmentioning
confidence: 73%
“…In vivo administration to rats to test potential treatment of erectile dysfunction [184,185] WAY 100635 16.4 D4 receptor agonist and 5HT1A antagonist; produces discriminative stimulus effects in rats [186,187] PD 168077 8.7 Selective D4 agonist, proerectile effect in rats [188]; tested in mice for memory consolidation studies [189] PNU 96415E 3 Tested for antipsychotic potential [190] Ro 10-5824 5.2 Selective D4 agonist, increases novel exploration in mice [191] NGD 94-1 3…”
Section: Dopamine-related Diseasesmentioning
confidence: 99%
“…Adding to the complexity, apomorphine, as a non-selective dopaminergic receptor agonist, affects several types of dopaminergic receptors among them D 1 , D 2 and D 4 (Brioni and Moreland, 2006;Brioni et al, 2004;Melis et al, 2005Melis et al, , 2006Schechter and Greer, 1987), whereas chronic treatment with apomorphine may change the balance between dopamine D 1 and D 2 receptors, favoring the D 1 type (Acerbo et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine is one of the main neurotransmitters involved in the central control of erectile functions, genital reflexes and male sexual behavior (Andersen et al, 2003;Argiolas and Melis, 2005;Giuliano and Rampin, 2000a,b;Giuliano and Allard, 2001;Heaton, 2000;Hull et al, 1986;Martino et al, 2005;Melis and Argiolas, 1995;Melis et al, 2006;Moses et al, 1995;Paredes and Agmo, 2004;Pehek et al, 1989;Succu et al, 2007). Apparently, the paraventricular hypothalamic nucleus, especially its oxytocinergic neurons, play an eminent role in the control of erectile function Melis, 2004, 2005;Martino et al, 2005;Succu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%